2021
DOI: 10.1186/s12905-021-01472-5
|View full text |Cite
|
Sign up to set email alerts
|

Does laparoscopic hysterectomy + bilateral salpingectomy decrease the ovarian reserve more than total abdominal hysterectomy? A cohort study, measuring anti-Müllerian hormone before and after surgery

Abstract: Background Decreased ovarian function and reserve is one of the complications of hysterectomy. In this study, we aimed to compare anti-müllerian hormone (AMH) levels between total abdominal hysterectomy (TAH), and total laparoscopic hysterectomy (TLH). Methods In this prospective cohort study, serum levels of AMH were compared between the groups undergoing TAH + bilateral salpingectiomy and TLH, in 66 patients (33 in each group) who referred to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…16 On the other hand, Tavana et al recently reported opposite findings of increased postoperative decline in AMH levels among women undergoing abdominal hysterectomy in a smaller sample (33 women per group). 17 Notably, in the latter report, women were aged 40–50 years, baseline AMH levels were overall low (400 pg/mL or less), and salpingectomies were performed in these patients. The conflicting data suggest that the precise surgical approach and possibly an independent role of salpingectomy may influence postoperative ovarian reserve, but effects may be transient and are incompletely understood.…”
Section: Discussionmentioning
confidence: 89%
“…16 On the other hand, Tavana et al recently reported opposite findings of increased postoperative decline in AMH levels among women undergoing abdominal hysterectomy in a smaller sample (33 women per group). 17 Notably, in the latter report, women were aged 40–50 years, baseline AMH levels were overall low (400 pg/mL or less), and salpingectomies were performed in these patients. The conflicting data suggest that the precise surgical approach and possibly an independent role of salpingectomy may influence postoperative ovarian reserve, but effects may be transient and are incompletely understood.…”
Section: Discussionmentioning
confidence: 89%
“…Other invasive and minimally invasive treatments for leiomyomas, including uterine artery embolization and hysterectomy, may decrease ovarian reserve, and it is possible that myomectomy may affect ovarian reserve through similar mechanisms, such as interrupting the collateral vasculature that supplies the ovaries through cautery, sutures, or temporary occlusion. [13][14][15][16][17][18] The use of a tourniquet to minimize blood loss during myomectomy transiently decreases blood supply to the ovaries and could potentially harm ovarian reserve. [19][20][21][22] The few studies that have assessed a possible effect of myomectomy on ovarian reserve are limited by small sample sizes, short-term follow-up, or unspecified surgical route and details.…”
Section: Resultsmentioning
confidence: 99%
“…Comparing AMH levels between total abdominal hysterectomy and total laparoscopic hysterectomy, Tavana et al found a significant decrease in this hormone level after both methods of hysterectomy. However, a lower level of AMH was noted in the total abdominal hysterectomy group [ 22 ].…”
Section: Discussionmentioning
confidence: 99%